The transformation of American abolitionism : fighting slavery in the early Republic - Newman, Richard S. (The University of North Carolina Press, 2002)
A history of how abolitionism evolved from an elite and conservative movement to a radical, grassroots reform cause. It traces the development of the abolitionist movement from the 1770s to the 1830s, covering the attitudes and actions which made it the radical cause we think of it as today.